2013
DOI: 10.5578/mb.4773
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Adenoviruses in Children with Lower Respiratory Tract Infections

Abstract: ÖZETAdenoviruslar tüm dünyada epidemik, endemik veya sporadik olarak yıl boyunca ve her yaşta görü-lebilen akut solunum yolu enfeksiyonlarına yol açmaktadır. Adenovirus enfeksiyonları alt solunum yollarına ilerleyerek, bronşit, bronşiyolit ve pnömoni tablolarına da sebep olmaktadır. Bu çalışmada alt solunum yolu enfeksiyonu (ASYE) olan çocuklarda etken olarak adenovirusların hücre kültürü, polimeraz zincir reaksiyonu (PCR) ve direkt floresan antikor testi (DFA) yöntemleriyle araştırılması ve sonuçların hastala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
0
6
0
6
Order By: Relevance
“…Samples like nasopharynx aspirates, eluate, and trachea-alveol irrigation are beneficial; however, implementation is relatively difficult. Flexible flocked swabs that have entered into application in recent years provide convenience and ease in taking samples and handling them and have been successfully and quite commonly used in isolating respiratory tract viruses (16,17).…”
Section: Diagnosismentioning
confidence: 99%
“…Samples like nasopharynx aspirates, eluate, and trachea-alveol irrigation are beneficial; however, implementation is relatively difficult. Flexible flocked swabs that have entered into application in recent years provide convenience and ease in taking samples and handling them and have been successfully and quite commonly used in isolating respiratory tract viruses (16,17).…”
Section: Diagnosismentioning
confidence: 99%
“…Although the gold standard diagnostic test is cell culture, it is time consuming and quite laborious. In recent years, polymerase chain reaction (PCR) test has been widely used in the diagnosis of adenovirus, since viral DNA can be detected by rapid molecular methods (2). It is reported that its incidence is higher in children aged between 6 months and 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that its incidence is higher in children aged between 6 months and 5 years. Although it rarely causes acute respiratory distress syndrome (ARDS), it may be more fatal compared to other factors (1,2). In this article, we have discussed a fatal adenovirus infection in spite of extracorporeal supportive treatments in a pediatric patient who had a pre-diagnosis of bacterial pneumonia and progressed rapidly to ARDS with clinical and laboratory findings.…”
Section: Introductionmentioning
confidence: 99%
“…yöntemlerle saptanabilmesi nedeniyle son yıllarda polimeraz zincir reaksiyonu (PCR) testi adenovirüs tanısında yaygın olarak kullanılmaktadır (2). Altı ay-5 yaş arası çocuklarda görülme sıklığının daha fazla olduğu belirtilmektedir.…”
unclassified
“…Altı ay-5 yaş arası çocuklarda görülme sıklığının daha fazla olduğu belirtilmektedir. Akut solunum sıkıntısı sendromu (ARDS)'na nadiren sebep olsa da diğer etkenlerle karşılaştırıldığında daha ölümcül seyredebilmektedir (1,2). Bu makalede klinik ve laboratuvar bulguları ile bakteriyel pnömoni ön tanısı alan ve hızlı bir şekilde ARDS'ye ilerleyen çocuk hastada, vücut dışı destek tedavilerine rağmen ölümcül seyreden adenovirüs enfeksiyonundan bahsedilmiştir.…”
unclassified